If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying log(2)(7x + 6) = 3 Reorder the terms: glo * 2(6 + 7x) = 3 Reorder the terms for easier multiplication: 2glo(6 + 7x) = 3 (6 * 2glo + 7x * 2glo) = 3 (12glo + 14glox) = 3 Solving 12glo + 14glox = 3 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Reorder the terms: -3 + 12glo + 14glox = 3 + -3 Combine like terms: 3 + -3 = 0 -3 + 12glo + 14glox = 0 The solution to this equation could not be determined.
| (2x-5y)-(x+y)= | | 6x+4=6x-3 | | 1.75x^3+2.5x^2=6.25x | | -17+x=63 | | (3x+5)-7=42 | | 4(1+4n)=-124 | | 3x+6=4x-17 | | 27x+9y=54 | | 4x-6-9x+1=0 | | 8(x-6)=-88 | | -3x+36=-18 | | 6b^2+13b-63= | | 3/4*2/7= | | 8*9n=96 | | 19-(2x+3)=2(x+3) | | 2(x+1)=3x-15 | | 10y-2=3y+33 | | 3(5+4b)-2=0 | | 3z-4=5z-1 | | 4+a=16 | | 82=2(-1+7m) | | 7+3.2=3.2x | | 2b+8=0 | | 6y-4(2-3(4y-1))=-17 | | A+81=9z-7 | | 7b+13=35-4b | | 166=2*36+2W | | 27x^2+37x=0 | | 3=2(-2)-y | | 4x-12=3.5 | | 10+x=1x+2 | | 3(x+4)-2=3x+10 |